Multi-wavelength bismuth-based erbium-doped fiber laser based on four-wave mixing effect in photonic crystal fiber - Parvizi, R.; Harun, Sulaiman Wadi; Shahabuddin, N.S.; Yusoff, Z.; Ahmad, Harith (Elsevier, 2010)
A stable multi-wavelength erbium-doped fiber laser based on four-wave mixing (FWM) in a photonic crystal fiber (PCF) is demonstrated in this paper. The phase matching condition for four-wave mixing in the photonic crystal fiber has been enhanced using a seed signal and a polarisation controller to control the states of polarisation in the ring laser cavity. At a maximum pump power of 1480 nm, 5 lines are observed with nearly 2.15 nm spacing between the lines, and with a signal to noise ratio of more than 20 dB. The number of channels and wavelength spacing can be controlled by varying the output coupler ratio. (C) 2010 Elsevier Ltd. All rights reserved.